Functional Genomics of Cardioprotection by Ischemic Conditioning and the Influence of Comorbid Conditions: Implications in Target Identification - V. Varga, Zoltan; Giricz, Zoltan; Bencsik, Peter; Madonna, Rosalinda; Gyongyosi, Mariann; Schulz, Rainer; Mayr, Manuel; Thum, Thomas; G. Puskas, Laszlo; Ferdinandy, Peter (Current Drug Targets, 2015)
Ischemic heart disease including myocardial infarction develops on the basis of several risk-factors and comorbidities such as obesity, diabetes, hypertension, and hypercholesterolemia. Ischemic heart disease is the leading cause of mortality worldwide, therefore, identification of novel drug targets for cardioprotection is of great importance. Ischemic preconditioning, postconditioning, and remote conditioning trigger endogenous cardioprotective mechanisms that render the heart more resistant to lethal ischemic-reperfusion injury. However, major cardiovascular co-morbidities such as hyperlipidemia, diabetes, and their co-medications interfere with these cardioprotective mechanisms thereby limiting the efficacy of cardioprotective ischemic conditioning maneuvers. Ischemia reperfusion injury and cardioprotection by conditioning have been shown to affect global myocardial gene expression profile at the transcript level. Further understanding and the comprehensive analysis of the cardioprotective gene expression fingerprint in normal, protected, and in comorbid conditions may lead to identification of novel molecular targets for cardioprotection.
Keywords: microRNA